International Arctic Petroleum Cooperation Barents Sea Scenarios - Bourmistrov, Anatoli; Mellemvik, Frode; Bambulyak, Alexei; Gudmestad, Ove; Overland, Indra; Zolotukhin, Anatoly (Routledge Studies in Environmental Policy, 2015)
The Arctic region contains large amounts of natural resources considered necessary to sustain global economic growth, so it is unsurprising that it is increasingly susceptible to political, economic, environmental, and even military conflicts. This book looks in detail at the preconditions and outlook for international cooperation on the development of Arctic petroleum resources, focusing on Norwegian-Russian cooperation in the Barents Sea towards 2025. The authors provide a cross-disciplinary approach including geopolitical, institutional, technological, corporate and environmental perspectives to analyse the underlying factors that shape the future development of the region. Three future scenarios are developed, exploring various levels of cooperation and development influenced by and resulting from potential political, commercial and environmental circumstances. Through these scenarios, the book improves understanding of the challenges and opportunities for Arctic petroleum resource development and promotes further consideration of the possible outcomes of future cooperation. The book should be of interest to students, scholars and policy-makers working in the areas of Arctic studies, oil and gas studies, energy security, global environmental governance, environmental politics and environmental technology. Chapter 1 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138783263_oachapter1.pdf Chapter 2 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138783263_oachapter2.pdf Chapter 6 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138783263_oachapter6.pdf